(untitled) (Journal of Applied Learning and Teaching, 2020)
This study investigates the conversation between a teacher and a group of students in a Mandarin lesson at a secondary school in London. The specific task for that lesson was to nominate a team leader for the presentation of a Chinese city. By applying conversation analysis, this study reveals the asymmetric power between the teacher and students and how the teacher managed the teacher-student rapport in the class. This study also presents the dynamics in the class and the linguistic features of the conversation; the teacher eventually exerted reward, coercive, expert and legitimate power during the lesson. The study focuses on how the teacher-student rapport was challenged concerning students’ identities, educational goals, sociality right and obligations. Furthermore, this study reveals that the teacher’s questions were more referential than initial and presents how an experienced teacher managed the class and achieved the educational goal.